Cohabitation in the Penal Code Reform in Relation to Religious and Customary Laws - Muhammad Zul; Andi Mulyono; Alice Ance Bonggoibo (Indonesian Scientific Publication, 2024)
The main purpose of this research is to prevent vigilantism, integrate customary law with positive law, and protect the values of decency and morals of Indonesian society. The formulation of the problem includes how customary law and religion affect the view and handling of cohabitation, and how the reform of the Criminal Code can provide solutions to this phenomenon. The research method used is a normative approach, with analysis of relevant literature, laws and regulations, and field data. The contribution of this research lies in filling the void of previous studies that have not specifically examined cohabitation in the reformation of the Criminal Code in relation to religious law and customary law. The novelty of this research is that there is a solution to prevent cohabitation through the approach of customary law and religious law. The findings show that criminalisation of cohabitation is necessary to maintain moral values and prevent further criminal acts. The research also found that the implementation of the new Criminal Code that regulates cohabitation can provide effective protection and prevent vigilantism.